2005
DOI: 10.1002/hep.20732
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis: Effect of symptoms and cirrhosis on natural history and outcome

Abstract: Although the natural history of autoimmune hepatitis (AIH) has been characterized, little is known about patients who present asymptomatically. Consequently, whether they require immunosuppressive therapy with its associated complications is unclear. To compare the natural history of asymptomatic AIH with symptomatic AIH, a large cohort of patients from a single center was examined. All patients with a clinical diagnosis of AIH were reassessed using the revised criteria of the International Autoimmune Hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
278
3
21

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(326 citation statements)
references
References 24 publications
24
278
3
21
Order By: Relevance
“…The presence of cirrhosis at the time of presentation has also been associated with an adverse prognosis [18].…”
Section: Histological Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of cirrhosis at the time of presentation has also been associated with an adverse prognosis [18].…”
Section: Histological Findingsmentioning
confidence: 99%
“…They revealed that untreated AIH has a poor prognosis with 5-and 10-year survival rates of 50 and 10%, respectively, whereas treatment with prednisolone is associated with excellent short-and long-term survival [34,35]. Up to 30% of adult patients have histological features of cirrhosis at diagnosis [18,36] and progression of fibrosis can occur in patients with inflammatory activity despite steroid therapy [18]. The presence of cirrhosis at baseline significantly increases the risk of subsequent death or liver transplantation [18,37].…”
Section: Natural Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Los autoanticuerpos no tienen papel en la monitorización. La presencia de cirrosis es el principal factor de mal pronóstico 12 .…”
Section: Caso Clínicounclassified